1974
DOI: 10.1111/j.1949-8594.1974.tb08986.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Cognitive Preferences of Pre‐Service Elementary Teachers

Abstract: 691The scale on the larger wheel could represent the chords of the old progression and then the scale of the new progression would be on the smaller wheel. Line up the symbol of the old key (on the large disc) with the symbol of the new key (on the small disc). Now all the chords used in the old key will line up with the chords to be used in the new key.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, in the physical science subtests, preferences for Questioning and Principles were higher than preferences for Recall and Application. Atwood and Rogers (1974), using a cognitive preference test which measured only R, Q, and A, found that elementary education students ( N = 201) at the end of their science and social science methods courses displayed a connitive preference pattern with, on the average, a relatively high preference for A, medium preference for Q and low preference for R. It is impossible to determine whether the differences between their results and the results of the present study stem from differences between the two tests or from differences between the samples tested. About half of the items in the test used by Atwood and Rogers dealt with social sciences.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the physical science subtests, preferences for Questioning and Principles were higher than preferences for Recall and Application. Atwood and Rogers (1974), using a cognitive preference test which measured only R, Q, and A, found that elementary education students ( N = 201) at the end of their science and social science methods courses displayed a connitive preference pattern with, on the average, a relatively high preference for A, medium preference for Q and low preference for R. It is impossible to determine whether the differences between their results and the results of the present study stem from differences between the two tests or from differences between the samples tested. About half of the items in the test used by Atwood and Rogers dealt with social sciences.…”
Section: Resultsmentioning
confidence: 99%